PEMBENTUKAN CITRA POSITIF H. SAHBIRIN NOOR MELALUI GELAR PAMAN BIRIN - Muhammad Ilham Kurniawan (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2021)
Democracy is a system that makes the people as holders of power, Indonesia is a democratic country that determines leaders through general elections for both president and regional head. In the 2015 election, a candidate for governor of South Kalimantan Province H. Sahbirin Noor used the title Paman Birin as an Empathy and Homophily approach to build a positive image of himself, it is interesting to research with the title